NEW EFFORTS FOR A REVISION AND CORRELATION OF THE AMMONITE FAUNA OF THE NEUBURG FORMATION (TITHONIAN, SW GERMANY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Ammonites collected bed-by-bed by the late K.W. Barthel allow a high biostratigraphic resolution of the succession of the Neuburg Formation (Unterhausen Member) into 2 regional Biochronozones (Ciliata Zone, Palmatus Zone) and 5 ammonite faunal horizons. The new finds are important for a revision of the taxa described in the monographs of Th. Schneid. The fauna consists of a Submediterranean stock of perisphinctids, together with some Tethyan and Subboreal faunal elements. Especially the co-occurring Tethyan immigrants Volanoceras schwertschlageri, Virgatosimoceras rothpletzi, and Richterella cf. richteri point to a correlation of basal parts of the Neuburg Formation with the Fallauxi Zone. In the younger faunal horizons the Tethyan influx strongly decreases, so that a direct correlation with the Tethyan standard zonation is impossible. Nevertheless, the ammonites of the younger horizons allow a correlation with the Subboreal zonal scheme.